Sex and love - Hemming, James, 1909-; Maxwell, Zena (London : Heinemann educational books, 1973)
Presents historical, cultural, biological, psychological, attitudinal, and other aspects of sex and love as dimensions of human experience.
includes index
Keywords: Sex; Love; Sexual ethics; Love